Rescue of ancestral and cultural practices in the preparation of casabe and mañoco in the Piapoco and Sikuani community - Rivera Reyes, Flor Ángela (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The Pedagogical and Technological University of Colombia, the Faculty of Distance Studies, and the Basic Education Program fulfill in the Guainía region with the professional training of Indigenous teachers Piapoco and Sikuani, who are able to manage and foster educational, organizational and leadership processes in their communities, promoting a vision towards the valorization, recovery and strengthening of culture, territory, environment, and ancestral knowledge of practices in their life plan, that defend and promote respect for Interculturality, which lead to an autonomy for the recognition of the collective rights and duties of the community.